1988
DOI: 10.1017/s0266467400002807
|View full text |Cite
|
Sign up to set email alerts
|

Input of wind–dispersed seeds into light–gaps and forest sites in a Neotropical forest

Abstract: A total of 52,467 wind-dispersed seeds from 14 tree and 32 liana species fell into 1720 seed traps in 43 paired light-gap and adjacent forest sites on Barro Colorado Island, Panama. Summed at the community level, many more wind-dispersed seeds were collected from light-gaps (61%) than from forest sites (39%). They accumulated from March through May, 1984 to a density of 328 m-2 in gaps and 207 m-2 in forest sites. In contrast, only 33% of the total of 2782 non-wind-dispersed seeds were collected in gaps. Due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
4
12

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 10 publications
1
51
4
12
Order By: Relevance
“…Several studies have also suggested that wind-dispersed seeds may arrive in gaps at higher densities than in adjacent forests due to small-scale turbulence, but evidence remains equivocal (e.g. Augspurger & Franson 1988;Bailing et al 2002). Much less noted is the opposite pattern -disproportionate dispersal to understorey sites.…”
Section: Patternsmentioning
confidence: 99%
“…Several studies have also suggested that wind-dispersed seeds may arrive in gaps at higher densities than in adjacent forests due to small-scale turbulence, but evidence remains equivocal (e.g. Augspurger & Franson 1988;Bailing et al 2002). Much less noted is the opposite pattern -disproportionate dispersal to understorey sites.…”
Section: Patternsmentioning
confidence: 99%
“…Entre vários métodos para o estudo de eventos fenológicos, diversos autores utilizaram peneiras coletoras para estudos da chuva de sementes (Jackson 1981, Augspurger & Franson 1988, Schupp 1990, Lugo & Frangi 1993, Walker & Neris 1993, Chapman et al 1994, Greene & Johnson 1994, Herrera et al 1994, White 1994) e de aspectos da fenologia (Jackson 1978, Wright & van Schaik 1994 em comunidades vegetais nos trópicos. Entre as vantagens apresentadas para este método está a facilidade de distinção entre botões e flores e entre frutos imaturos e maduros, dificilmente distingüíveis pela simples observação em algumas espécies (Bullock & Sollis-Magalhanes 1990).…”
Section: Introductionunclassified
“…As in Panama lowland terra firme forest and gaps, most of the seed rain was from animal-dispersed species, but more wind-dispersal species were found in the gaps compared to the forests (Augspurger and Franson 1988). Seeds were again mainly from species-rich families such as Melastomataceae, Piperaceae, and Rubiaceae.…”
Section: Comparison To Other Neotropic Studiesmentioning
confidence: 92%
“…The forests themselves were 200 m apart. In the center of each forest area and each gap area, seed traps were established and soil samples were taken in late June 2004 (Augspurger and Franson 1988) for a total of 20 microsites (2 forest-types [terra firme vs. várzea] × 2 openness-types [gap vs. non-gap/intact forest] × 5 replicates). Seed rain was collected using standard 1 m 2 area seed traps (see Myster and Sarmiento 1998) placed in the center of microsite and identified to species for a total sampling area of 20 m 2 .…”
Section: Methodsmentioning
confidence: 99%